2006
DOI: 10.1063/1.2168044
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of bonding energy for the interfaces in Cu metallization systems

Abstract: The toughness of two different interfaces in Cu metallization systems (Cu∕barrier metals and Cu∕cap layer) was evaluated by developed techniques. To establish the measurement technique at first, the effect of Cu film thickness on the evaluated toughness of the interface between Cu and barrier metal was examined. A small-scale yielding condition was realized even with ductile thin-film systems, and the toughness obtained was almost independent of the film thickness. The difference in the interface toughness amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[12][13][14][15] Figure 4 shows the finite element model used in the numerical simulation. [12][13][14][15] Figure 4 shows the finite element model used in the numerical simulation.…”
Section: B Numerical Simulation For Evaluating Interface Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] Figure 4 shows the finite element model used in the numerical simulation. [12][13][14][15] Figure 4 shows the finite element model used in the numerical simulation.…”
Section: B Numerical Simulation For Evaluating Interface Adhesionmentioning
confidence: 99%
“…Since the virtual crack propagation method is not suitable for analysis that includes plastic deformation, the interface adhesion was evaluated using the crack closure method expressed by [12][13][14][15] :…”
Section: Effect Of Plastic Deformation In Copper Layermentioning
confidence: 99%
“…Recently, Kamiya and coworkers have developed a micronscale evaluation method. 11,12) In this method, small blocks of the insulation layer material on the Cu conductive layer were used as specimens, [13][14][15] and crack extension was simulated by the finite element method to evaluate the Cu/SiN interface adhesion energy G c . [16][17][18] In our previous study, three-dimensional elastic crack propagation simulation and the crack-closer method were used to evaluate interface adhesion energy, G c .…”
Section: Introductionmentioning
confidence: 99%
“…6 Sputtered Cu atoms leave the target with relatively high energy (a few eV) but lose it rapidly due to collisions with the background gas. It had been demonstrated that Cu forms a much stronger interface with the barrier for sputter-deposited films compared to evaporated films.…”
Section: Introductionmentioning
confidence: 99%